1987
DOI: 10.1016/0014-5793(87)80885-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine cells share expression of N‐CAM with neurones

Abstract: The expression of the neural cell adhesion molecule, N-CAM, was examined in the anterior lobe of rat hypophysis by immunocytochemistry at light and electron microscope levels. In addition, N-CAM antigenic determinants present in adrenal medulla, anterior hypophysis and PC12 cells were compared by immunoblotting with those found in cerebellum. All secretory cells in the anterior hypophysis were found to be N-CAM positive on their surfaces, but not all of the three polypeptide determinants typical of cerebellum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The scarcity of junctional complexes, at least in our culture system, indicates that they are not the cause of reconstructed topographic affinity between hormone-producing cells. Some cell adhesion molecules have been identified in the rat anterior pituitary, including NCAM (Langley et al, 1987;Berardi et al, 1995) and PB-cadherin (Sugimoto et al, 1996). Spangler and Delidow (1998) observed P-and N-cadherin expression in PRL-producing rat pituitary 253-1 cells, and Heinrich et al (1999) reported that N-cadherin mediates cell aggregation in rat somatolactotropic GH 3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of junctional complexes, at least in our culture system, indicates that they are not the cause of reconstructed topographic affinity between hormone-producing cells. Some cell adhesion molecules have been identified in the rat anterior pituitary, including NCAM (Langley et al, 1987;Berardi et al, 1995) and PB-cadherin (Sugimoto et al, 1996). Spangler and Delidow (1998) observed P-and N-cadherin expression in PRL-producing rat pituitary 253-1 cells, and Heinrich et al (1999) reported that N-cadherin mediates cell aggregation in rat somatolactotropic GH 3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…3a). Thus these cells express the same NCAM isoform, which appeilrs to be the most characteristic NCAM isoform in rat endocrine tissues and rat endocrine tumor eelllines [6,7] and in these endoerine tissues. Lane 7 (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The recent observation of neural cell adhesion molecules (NCAMs) in endocrine cells [6,7] and the neuroendocrine nature of certain lung cancer types (cf. [1]) suggested that these surface molecules may be pres-296 ent in a significant fraction of lung tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NCAMs were first found in the nervous system, but subsequently were also found in polypeptide hormoneand steroid-producing endocrine cells [10][11][12][13][14][15]. NCAMs allow the formation of cell clusters by auto-adhesion of neighboring NCAM-bearing cells.…”
Section: Introductionmentioning
confidence: 99%